ANALISIS PERAN DESA ADAT TERHADAP PEMBANGUNAN DESA WISATA DI DESA SERANGAN KOTA DENPASAR - Suryawarman, A.A Ngurah Rameswara; Yashinta, Putu Nomy; Winaya, I Ketut (CITIZEN CHARTER, 2020)
ABSTRACT Bali Province has two special organizations or institutions at the village level. The organization is the Desa Dinas and Desa Adat. The purpose of this study was to find out about the role of Indigenous Villages, especially in Serangan Village in the case of Tourism Village Development. The results showed that the Indigenous Village especially as the manager of Serangan Tourism Village is one of the facilities or facilitator providers for the units owned by Serangan Village such as the granting of land given to the Turtle Conservation. Bendesa Adat also plays a role in building a facility that can open jobs for the community, for example Pier. Lack of awareness of the people of the village of Serangan Village will cleanliness of the environment. This causes the Customary Village to be able to straighten out and be able to reduce the problem slowly. KeyWords: Tourism Village, Indigenous Village, The Role of Indigenous Villages, Role Theory